2020
DOI: 10.1111/ap.12472
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between disconfirmed expectations of motherhood, depression, and mother–infant attachment in the postnatal period

Abstract: Objective: The postnatal period can be both a rewarding and challenging time. Research has found that experiences of motherhood that are less positive than expected are associated with depressive symptoms, however, no known study to date has examined expectations across the separate domains of motherhood and how they impact on attachment. The aim of this cross-sectional study was to investigate whether discrepancies in a mother's expectations regarding their infant, levels of support, and sense of self and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
1
7
1
Order By: Relevance
“…If women have set this standard for themself and cannot live up to it once they become a mother, guilt and shame may arise. This can be a precursor to depressive symptoms and diagnosis of postpartum depression (Haga et al, 2012;Harwood et al, 2007;Kauppi et al, 2012;Law et al, 2021;Liss et al, 2013;Rizzo & Watsford, 2020). Haga et al (2012) found similar rigid responses in a group of first-time mothers and noted that mothers were either relaxed or controlled in their approach to motherhood.…”
Section: Discussionmentioning
confidence: 86%
“…If women have set this standard for themself and cannot live up to it once they become a mother, guilt and shame may arise. This can be a precursor to depressive symptoms and diagnosis of postpartum depression (Haga et al, 2012;Harwood et al, 2007;Kauppi et al, 2012;Law et al, 2021;Liss et al, 2013;Rizzo & Watsford, 2020). Haga et al (2012) found similar rigid responses in a group of first-time mothers and noted that mothers were either relaxed or controlled in their approach to motherhood.…”
Section: Discussionmentioning
confidence: 86%
“…For some mothers, similar to findings from Prikhidko and Swank (2018), there is a struggle between what they thought about motherhood and what they experienced. Rizzo and Watsford (2020) found that for new mothers, when reality did not match expectations there was an increase in depression, anxiety, and stress. In this study, the participants who noted this theme concluded that the reality was more meaningful than what they had expected.…”
Section: Discussionmentioning
confidence: 96%
“…Participants reported experiences of second guessing themselves, questioning themselves, and comparing themselves to others. As warned by Prikhidko and Swank (2018) and Rizzo and Watsford (2020) navigating systemic influences and the perceptions of the ideal mother versus realities of mothering can contribute to mental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations